Switch maintenance endocrine therapy plus bevacizumab after bevacizumab plus paclitaxel in advanced or metastatic oestrogen receptor-positive, HER2-negative breast cancer (BOOSTER): a randomised, open-label, phase 2 trial. Issue 5 (May 2022) - Saji, Shigehira; Taira, Naruto; Kitada, Masahiro; Takano, Toshimi; Takada, Masahiro; Ohtake, Tohru; Toyama, Tatsuya; Kikawa, Yuichiro; Hasegawa, Yoshie; Fujisawa, Tomomi; Kashiwaba, Masahiro; Ishida, Takanori; et al.
Summary: Background: Anticancer treatment regimens typically cause unpleasant side-effects. We aimed to investigate the benefit of switch maintenance endocrine therapy plus bevacizumab after fixed cycles of first-line induction chemotherapy with weekly paclitaxel plus bevacizumab in patients with oestrogen receptor (ER)-positive, HER2-negative advanced or metastatic breast cancer. Methods: BOOSTER was a prospective, open-label, multicentre, randomised, controlled, phase 2 study done in 53 hospitals in Japan. Eligible patients were women aged 20–75 years, with an Eastern Cooperative Oncology Group performance status of 0–1, who had not received chemotherapy for ER-positive, HER2-negative advanced or metastatic breast cancer. All patients received four to six cycles (in which 4 weeks of treatment constitute one cycle) of weekly paclitaxel plus bevacizumab induction therapy (weekly paclitaxel 90 mg/m 2, administered intravenously on days 1, 8, and 15 of each cycle, plus bevacizumab 10 mg/kg administered intravenously on days 1 and 15 of each cycle; first registration). Patients with a complete response, partial response, or stable disease after induction therapy (responders) were then randomly assigned (1:1) using the randomisation enrolment form to either continue weekly paclitaxel plus bevacizumab or switch to maintenance endocrine therapy (an aromatase inhibitor or fulvestrant with or without ovarian-function suppression) plus bevacizumab. Randomisation was stratified by induction therapy period, response to induction therapy, age, history of endocrine therapy, and study site. Patients could receive weekly paclitaxel plus bevacizumab reinduction if they had disease progression with maintenance endocrine therapy plus bevacizumab. The primary endpoint was time to failure of strategy (TFS). Efficacy and safety analyses were done in all treated patients (full analysis set). This study is registered with ClinicalTrials.gov, NCT01989780, and registration and follow-up are closed. Findings: Between Jan 1, 2014, and Dec 31, 2015, we enrolled 160 patients who began weekly paclitaxel plus bevacizumab induction therapy. 125 (78%) patients (responders) were randomly assigned to endocrine therapy plus bevacizumab (n=62; n=61 in the full analysis set) or weekly paclitaxel plus bevacizumab (n=63; n=63 in the full analysis set). Among 61 patients in the switch maintenance endocrine therapy plus bevacizumab group, 32 (52%) were reinitiated on weekly paclitaxel plus bevacizumab. At a median follow-up of 21·3 months (IQR 13·0–28·2), TFS was significantly longer in the endocrine therapy plus bevacizumab group than in the weekly paclitaxel plus bevacizumab group (median 16·8 months [95% CI 12·9–19·0] vs 8·9 months [5·7–13·8]; hazard ratio 0·51 [0·34–0·75]; p=0·0006). The most common grade 3–4 non-haematological adverse events after randomisation were proteinuria (in ten [16%] of 61 patients in the endocrine therapy plus bevacizumab group vs eight [13%] of 63 patients in the weekly paclitaxel plus bevacizumab group), hypertension (six [10%] vs six [10%]), and peripheral neuropathy (one [2%] vs six [10%]). One treatment-related death was reported in the weekly paclitaxel plus bevacizumab group (duodenal ulcer perforation). Interpretation: Switch to maintenance endocrine therapy plus bevacizumab with the possibility of weekly paclitaxel reinduction if needed is an efficacious alternative, with a better safety profile, to continuing weekly paclitaxel plus bevacizumab in patients with ER-positive, HER2-negative advanced or metastatic breast cancer who have responded to induction therapy. Funding: Chugai Pharmaceutical. Translation: For the Japanese translation of the abstract see Supplementary Materials section.